KNOWLEDGE SHARING MEMEDIASI PENGARUH KEADILAN ORGANISASI TERHADAP PERILAKU INOVATIF KARYAWAN PADA INDUSTRI KERAJINAN KAYU - Sriwahyuni, Made Bintang; Wibawa, I Made Artha (E-Jurnal Manajemen, 2021)
Human Resources are an important element in an organization and required to be innovative, provide new ideas or ideas that can be a competitive advantage for the company itself. This research was conducted to determine effect of organizational justice on employee innovative behavior with knowledge sharing as a mediating variable at Wood Craft Industry in Gianyar Regency with a sample size of 94 employees through the saturated sample method. Data collection was carried out through interviews and questionnaires. The data analysis used is Path Analysis. The results show that organizational justice has a positive and significant effect on employee innovative behavior, organizational justice has a positive and significant effect on knowledge sharing, knowledge sharing mediates between organizational justice and employees' innovative behavior. Theoretically, this study also provides an understanding that organizational justice will better influence employee innovative behavior if it is mediated by knowledge sharing. Keywords: Organizational Justice, Employee Innovative Behavior, Knowledge Sharing.